Revit : rendering and visualization - Cotey, Ed (InfiniteSkills, 2014)
"In this Revit - Rendering and Visualization training course, expert author Ed Cotey teaches you how to set up and process photorealistic visuals using the tools available in Revit Architecture. Using these tools, you will gain a better understanding of what the project will look like before it is built. This training course is designed for users that already have a basic understanding and working knowledge of Revit Architecture. You will start by learning the basics of creating and modifying camera views. Ed will show you how to view and modify a walkthrough from the outside and the inside. This video tutorial will cover topics that include: how to set the project into a true north view position, how to create solar studies, and how to render in Revit. Finally, Ed will share his tips, techniques, and suggestions to use when working with Revit's visualization tools. Once you have completed this computer based training course, you will be fully capable of using the tools available in Revit Architecture for your personal or work-related projects. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.